Relationship between natriuretic peptides and residual diuresis during continuous hemodiafiltration - Balík, Martin; Jabor, Antonín; Kolár, Michal; Pavlisová, Marie; Brest'an, Daniel; Hendl, Jan; Rychlík, Ivan; Pachl, Jan (Blood purification, 2003)
BACKGROUND: The reasons for the decrease or increase of urine output following the start of continuous venovenous hemodiafiltration (CVVHDF) have not yet been explained sufficiently. The renoprotective properties of natriuretic peptides were described. METHODS: The levels of atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) were measured in 23 mechanically ventilated patients before and during the first 48 h of CVVHDF. Samples were drawn both from the ports proximal and distal to the filter. The results were compared between the group where daily diuresis (Vu) remained low or decreased and the group where diuresis increased to the level of 1.5 ml x kg(-1) x h(-1) or higher after 48 h of treatment. Left ventricular dysfunction (LVD) was defined as LV ejection fraction below 40%. A control group consisted of 10 patients exposed to abdominal surgery. RESULTS: The average AVdiff (%) of ANP and BNP on filter were insignificant. Patients with increasing diuresis (n = 12) had significantly lower levels of both ANP (p < 0.001) and BNP (p < 0.005) than the patients with decreasing diuresis (n = 11). Significant correlations were revealed for ANP and Vu (p < 0.01) and for BNP and Vu (p < 0.05). The levels of both peptides were grossly elevated in comparison to controls and were predictive of survival. The differences between cardiac and non-cardiac patients were significant both for ANP and for BNP. CONCLUSIONS: The elimination of ANP and BNP by the CVVHDF is negligible. The levels of natriuretic peptides are inversely related to Vu and predict survival. ANP and BNP levels correlate with left ventricular function even during acute renal failure and CVVHDF.
Keywords: Male; Survival Rate; Diuresis; Statistics, Nonparametric; neparametrická statistika; Natriuretic Peptides; prognóza; Adult; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; natriuretický peptid typu B; akutní poškození ledvin; hemodiafiltrace; Atrial Natriuretic Factor; diuréza; lidé; Ventricular Dysfunction, Left; ženské pohlaví; studie případů a kontrol; Humans; natriuretické peptidy; Natriuretic Peptide, Brain; atriální natriuretický faktor; prediktivní hodnota testů; dysfunkce levé srdeční komory; Acute Kidney Injury; Prognosis; Female; Hemodiafiltration; lidé středního věku; Predictive Value of Tests; míra přežití; Middle Aged